APPLICATION OF INTAKE FRACTION TO ESTIMATE EMISSION CONTRIBUTION: CASE STUDY OF COAL-FIRED POWER PLANT AND TRANSPORTATION EMISSIONS - Astri Utami, Inda
The increasing demand for electricity in Indonesia has led to coal-fired power plants (CFPPs) being a vital energy source, fulfilling a major portion of the country’s energy needs. However, CFPPs contribute substantially to air pollution and emitting harmful pollutants such as sulfur dioxide (SO?), nitrogen oxides (NO?), and particulate matter (PM). These pollutants are linked to severe health effects, including respiratory diseases, lung cancer, and cardiovascular conditions. In addition, the transportation sector is a major source of air pollution, particularly in urban and semi-urban areas where emissions from vehicles such as trucks, buses, and motorbikes further degrade air quality. To address these challenges, this study applies the intake fraction (IF) approach to evaluate the contribution of CFPP and transportation emissions in the study area. The study models CFPP X as a point source and the highway as a line source, integrating meteorological data and source characteristics into a Gaussian dispersion model. The research area is divided into 1x1 km grids to estimate intake fraction and inhaled dose values for each grid. Meteorological parameters, including wind speed, wind direction, and atmospheric stability, are incorporated into the model to account for pollutant dispersion dynamics. Atmospheric stability class B is used for daytime calculations to reflect slightly unstable conditions. Average wind speeds are adjusted for source height and wind speeds perpendicular to the highway are used to calculate transportation emissions. The results reveal distinct pollutant exposure patterns based on proximity to emission sources. For CFPP X, intake fraction values range between 10?? and 10?¹¹, with the highest values observed in grids nearest the CFPP, such as Grid B5. Transportation emissions, on the other hand, exhibit more localized impacts, with intake fraction values peaking near the highway. Grids such as G4, G5, and G6 record the highest intake fraction values due to heavy traffic and localized pollutant accumulation. Inhaled dose calculations further illustrate these differences in exposure. SO? inhaled doses from CFPP X range from 1.28 ?g/day in distant grids like I1 to 58.05 ?g/day in Grid B5, the latter being closest to the plant. For NO?, CFPP contributions range between 0.77 ?g/day and 35.16 ?g/day, while the highway contributes NO? doses up to 19.96 ?g/day in Grid G4. Combined NO? inhaled doses are highest in Grid G4, at 22.24 ?g/day, reflecting the cumulative effects of CFPP and transportation emissions. PM inhaled doses from CFPP X range from 0.12 ?g/day in distant grids to 5.54 ?g/day in Grid B5, while transportation emissions contribute PM10 doses of up to 0.38 ?g/day in Grid G4. The highest combined PM inhaled dose, 52.50 ?g/day, is observed in Grid G4, driven by transportation emissions. The intake fraction values for both CFPP and transportation emissions are similar in magnitude despite their different spatial impacts. Transportation emissions create highly localized pollution near major roads, posing immediate risks to nearby populations. In contrast, CFPP emissions disperse over a broader area, with declining concentrations as distance increases. These findings highlight the mitigation strategies needed for each source: localized controls for transportation emissions and regional interventions for CFPP emissions. This study underscores the utility of the intake fraction method in estimating emission source contribution and identifying high-risk areas. Even in the absence of ambient air quality monitoring data, the IF method provides a reliable framework for evaluating the contribution of various emission sources to population exposure.